The Role of Cadiak Tau Pandai in Randai Hiliran Gumanti District Solok Regency - Wiranda Putri, Septia; Wimbrayardi (Universitas Negeri Padang, 2023)
Cadiak Tau Pandai's role in Randai, Hiliran Gumanti District, and Solok Regency This study set out to identify the function of cadiak tau pandai in randai in the Hiliran Gumanti District of the Solok Regency. An approach known as the descriptive-qualitative one was used to perform this study. Through a review of the literature, observation, interviews, and documentation, data for this study was gathered. Reduction, presentation, and verification are the steps in data analysis. Finding out the components of randai and Cadiak Tau Pandai's function in randai in the Hiliran Gumanti District, Solok Regency, is the goal of this data verification. The outcomes demonstrated the role played by Cadiak Tau Pandai in Randai in the Solok Regency's Hiliran Gumanti District. This cadiak tau pandai serves as a stand-in for all male positions. These roles are filled by regular individuals, not by the offspring of officials. Additionally, the actors in this role are passed down from generation to generation. It takes one to four weeks, or a month, for them to rehearse. They are known as multipurpose characters. They can not only be characters in the Randai story but also drummers, comedians, and MC.